Chemical tagging with APOGEE: discovery of a large population of N-rich stars in the inner Galaxy - Schiavon, RP; Zamora, O; Carrera, R; Lucatello, S; Robin, AC; Ness, M; Martell, SL; Smith, VV; García-Hernández, DA; Manchado, A; Schönrich, R; Bastian, N; et al. (Oxford University Press, 2016)
Formation of globular clusters (GCs), the Galactic bulge, or galaxy bulges in general is an important unsolved problem in Galactic astronomy. Homogeneous infrared observations of large samples of stars belonging to GCs and the Galactic bulge field are one of the best ways to study these problems. We report the discovery by APOGEE (Apache Point Observatory Galactic Evolution Experiment) of a population of field stars in the inner Galaxy with abundances of N, C, and Al that are typically found in GC stars. The newly discovered stars have high [N/Fe], which is correlated with [Al/Fe] and anticorrelated with [C/Fe]. They are homogeneously distributed across, and kinematically indistinguishable from, other field stars within the same volume. Their metallicity distribution is seemingly unimodal, peaking at [Fe/H] ∼ −1, thus being in disagreement with that of the Galactic GC system. Our results can be understood in terms of different scenarios. N-rich stars could be former members of dissolved GCs, in which case the mass in destroyed GCs exceeds that of the surviving GC system by a factor of ∼8. In that scenario, the total mass contained in so-called ‘first-generation’ stars cannot be larger than that in ‘second-generation’ stars by more than a factor of ∼9 and was certainly smaller. Conversely, our results may imply the absence of a mandatory genetic link between ‘second-generation’ stars and GCs. Last, but not least, N-rich stars could be the oldest stars in the Galaxy, the by-products of chemical enrichment by the first stellar generations formed in the heart of the Galaxy.